IMMUNOLOGICAL CHARACTERISTICS OF INTRAUTERINE FLUSHES FROM THE UTERINE CAVITY OF INFERTILE PATIENTS WITH ADENOMYOSIS AND THEIR EFFECT ON THE OUTCOMES OF ART PROGRAMS - Виктория Васильевна Лихачева; Ольга Валентиновна Азарова; Людмила Владимировна Ренге; Екатерина Юрьевна Григорьева; Борис Александрович Лихачев; Борис Исаевич Айзикович (Мать и дитя в Кузбассе)
The purpose of the study – identification of immunological predictors of implantation failures in IVF programs in patients with diffuse grade 1-2 adenomyosis as part of uterine cavity flushes.